Polymer-Assisted Synthesis of Single and Fused Diketomorpholines - Králová, Petra; Benická, Sandra; Soural, Miroslav (ACS combinatorial science, 2019)
The synthesis of different diketomorpholines via N-acyl-3,4-dihydro-2 H-1,4-oxazine-3-carboxylic acids is reported in this article. The key intermediates were prepared using a convenient solid-phase synthesis starting from polymer-supported Ser( tBu)-OH. After subsequent sulfonylation with 4-nitrobenzenesulfonyl chloride (4-Nos-Cl), alkylation with an α-bromoketone, cleavage of the 4-Nos group and acylation with an α-halocarboxylic acids, acid-mediated cleavage from the resin yielded dihydrooxazine-3-carboxylic acids in high crude purities. Depending on the reaction conditions, exposure to base resulted in cyclization to either oxazino[3,4- c][1,4]oxazine-diones or 3-methylidenemorpholine-2,5-diones. Further reaction with triethylsilane-trifluoroacetic acid (TES/TFA) led to olefin reduction, in the case of oxazino[3,4- c][1,4]oxazine-dione with full control of the newly formed stereocenter.
Keywords: oxaziny; Cyclization; techniky syntézy na pevné fázi; Carboxylic Acids; stereoizomerie; Morpholines; Polymers; Molecular Structure; morpholine; morfoliny; silany; Silanes; bromoketone; Nitrobenzenes; polymery; nitrobenzeny; solid-phase synthesis; Acylation; acylace; kyseliny karboxylové; cyklizace; Trifluoroacetic Acid; Alkylation; serine; diketomorpholine; Stereoisomerism; molekulární struktura; Oxazines; alkylace; Solid-Phase Synthesis Techniques; kyselina trifluoroctová